Graphene-Based Lubrication for Tribological Applications: Nanolubricants and Self-lubricating Nanocomposites - (:unkn) unknown (My University, 2018)
In this work, the effects of graphene nanoplatelets (GNPs) additives on tribological properties of aluminum are investigated. The objective of this research is to investigate and explain the enhancement mechanisms of GNPs at the contact surface during tribological testing. The graphene nanoplatelets are studied both as an oil additive (Chapter I) and as a reinforcement (Chapter II) experimentally. The coefficient of friction (COF) and wear rate were identified using a pin-on-disk test setup. Mineral, organic, and synthetic oils are not always efficient enough to satisfy the demands of a high-performance lubricant; therefore, mixing additives with base fluids is an approach to improve the lubrication ability and to reduce friction and wear. In chapter I, GNPs are used as lubricant additives to make nanolubricants. Then, the combined effect of the material’s variables (GNPs loading, size, and dispersion stability) and tribo test’s variable (applied normal load) are investigated on COF and wear rate of aluminum. Tribological studies are all carried out in the boundary lubrication regime. Three-dimensional surface metrology is performed using an optical profilometer. Various surface analyses, including Scanning Electron Microscope (SEM), Energy-Dispersive X-ray Spectroscopy (EDX), and Raman Spectroscopy are performed to assess the chemical elements on the tested surfaces. The experimental and theoretical analyses show that GNPs are effective in reducing friction and wear, although, this positive effect is more influential at higher loads. Also, it is demonstrated that there is a critical concentration of GNPs, below which a reduced wear rate is not sustained. The proposed mechanism to describe the effect of GNPs in boundary lubrication condition is “reduced direct metal-metal contact area” at the contact surface. In other words, a material which has low shear strength layers sits between two contacting surfaces and separates the two sliding metal surfaces with no actual contact between them. This means that there is less formation of asperity junctions between the two surfaces. Although liquid-based lubricants are efficient enough in most tribological applications, there are circumstances, such as extreme environmental conditions such as high or low temperatures, vacuum, radiation, and high contact pressure in some aerospace applications, where no liquid lubricants can be present. In addition, interminable providing of lubricant at the contact surface is another challenge ahead. In order to respond to these challenges of using liquid oil at extreme environmental conditions, in chapter II of this dissertation, the synthesis and performance of self-lubricating aluminum matrix nanocomposite are evaluated (Chapter II). Aluminum powder is mixed with varying concentrations of GNPs and alumina nanoparticles to form a hybrid metal matrix nanocomposite. High-energy ball milling is conducted at room temperature while powders are immersed and protected by benzene bath. Degassing is accomplished by heating to 135oC. Consolidation of the powders is conducted by single action cold compaction and single action hot compaction. Pin-on-disk experiments are conducted to investigate the tribological behavior of aluminum matrix composites reinforced by GNPs and compare them with unreinforced aluminum. Then, the combined effect of material’s variables (reinforcement type and loading) and tribo test’s variable (applied normal load) were investigated on COF and wear rate of aluminum. SEM and EDX were performed to assess the stoichiometry of the elements on the tribo surfaces. In addition, Raman Spectroscopy and Transmission Electron Microscopy (TEM) were also performed to identify the bonding/interactions between the phases on the surface. Results imply that the COF and wear rate of composites decrease by embedding graphene nanoparticles due to reduction the real contact area between the mating surfaces by forming the lubricant. Besides, the addition of alumina particles in Aluminum/GNPs composites can further improve COF and wear rate because of rolling effect of alumina nanoparticles. Increasing the loading of GNPs reduces the COF, while there is an optimum concentration of GNPs, above and below which the wear rate is increased. In addition, the COF and wear of all composites decreases by increasing normal load. Based on the observations, multiple mechanisms are proposed to describe the improved tribological behavior of the synthesized self-lubricating nanocomposites. In addition to the reduced direct metal-metal contact area at the contact surface, the fact that the layered GNPs structure is exposed to at the contact surface keeps the surface lubricated. In other words, under sliding conditions, the transfer layer formation of the GNPs on the tribo surfaces acts as a solid lubricant film, which prevents direct contact between the mating surfaces. Additionally, it is experimentally confirmed that GNPs prevent the surface from oxygen diffusion, thereby reducing the amount of oxides which are harder and more abrasive at the contact surface. “Load bearing” of added alumina nanoparticles, in addition to the increased hardness of the matrix, is another proposed mechanism of wear resistance enhancement. It has been shown that an effective lubricant layer forms when the solid lubricant has a strong adhesion to the bearing surface; otherwise, this lubricant layer can be easily rubbed away and tends to have a very short service life. Raman data confirms the formation of Al4C3 bonds on the tribo layer under certain test conditions.
Keywords: Graphene; Nanocompoites; Nanolubricants; Self-lubricating; Tribology; Wear